Aging Does Not Exacerbate Muscle Loss During Denervation and Lends Unique Muscle-Specific Atrophy Resistance With Akt Activation - You, Jae-Sung; Chen, Jie (Frontiers in Physiology, 2021)
Sarcopenia, or age-related skeletal muscle atrophy and weakness, imposes significant clinical and economic burdens on affected patients and societies. Neurological degeneration, such as motoneuron death, has been recognized as a key contributor to sarcopenia. However, little is known about how aged/sarcopenic muscle adapts to this denervation stress. Here, we show that mice at 27months of age exhibit clear signs of sarcopenia but no accelerated denervation-induced muscle atrophy when compared to 8-month-old mice. Surprisingly, aging lends unique atrophy resistance to tibialis anteria muscle, accompanied by an increase in the cascade of mammalian target of rapamycin complex 1 (mTORC1)-independent anabolic events involving Akt signaling, rRNA biogenesis, and protein synthesis during denervation. These results expand our understanding of age-dependent stress responses and may help develop better countermeasures to sarcopenia.